Analisis Dampak Kekerasan Berbasis Gender Pada Ibu Rumah Tangga Pengidap HIV: A Descriptive Review - Sandrina Miranda Simon; Hastin Trustisari (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This literature review study is motivated by empirical phenomena describing instances of violence against housewives with HIV. The implications of such violence result in physical, psychological, social harm, and even death. This literature aims to theoretically describe the impacts and factors of gender-based violence on housewives with HIV. The literature review was conducted using a descriptive method on four articles obtained from Google Scholar. The results of the literature review indicate the presence of physical, psychological/emotional, sexual, and economic impacts on housewives with HIV who experience violence. Additionally, the factors contributing to violence against women include cultural, economic, legal, political, and personality factors. Patriarchal culture is identified as a key element that enables violence against housewives with HIV. Human rights must be upheld, and violence against women must be entirely prohibited in Indonesian society. Future researchers are encouraged to conduct broader studies to generalize the impacts of gender-based violence on housewives with HIV, as research on this topic is still very limited.